2020
DOI: 10.1002/smll.202001529
|View full text |Cite
|
Sign up to set email alerts
|

Ag2S‐CdS p‐n Nanojunction‐Enhanced Photocatalytic Oxidation of Alcohols to Aldehydes

Abstract: Selective oxidation of alcohols to aldehydes under mild conditions is important for the synthesis of high‐value‐added organic intermediates but still very challenging. For most of the thermal and photocatalytic systems, noble metal catalysts or harsh reaction conditions are required. Herein, the synthesis and use of Ag2S‐CdS p‐n nanojunctions as an efficient photocatalyst for selective oxidation of a series of aromatic alcohols to their corresponding aldehydes is reported. High quantum efficiencies (59.6% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…[58] This type of ultrathin nanosheet structurec an prevents urfaces ulfide ions from being oxidized, thereby effectively inhibiting photocorrosion. In addition, coupling CdS with other semiconductors, such as Ti 3 C 2 T x , [42a] Ni 2 S, [59] W 2 S, [60] ZnS, [61] Ag 2 S, [62] and WO 3 , [63] is an effective method to suppresst he recombination of photoinduced chargepairs. The crystal phase structure and crystallinity of the Fe 3 O 4 / PDA/CdS composite catalysth ave ag reat influence on its photocatalytic activity.X RD can be used to characterizet he crystal phase structure and crystallinity of the photocatalyst.F igure 1 shows ac omparison of the XRD results of pure CdS nanosheets,p ureF e 3 O 4 NPs, and Fe 3 O 4 /PDA/CdS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[58] This type of ultrathin nanosheet structurec an prevents urfaces ulfide ions from being oxidized, thereby effectively inhibiting photocorrosion. In addition, coupling CdS with other semiconductors, such as Ti 3 C 2 T x , [42a] Ni 2 S, [59] W 2 S, [60] ZnS, [61] Ag 2 S, [62] and WO 3 , [63] is an effective method to suppresst he recombination of photoinduced chargepairs. The crystal phase structure and crystallinity of the Fe 3 O 4 / PDA/CdS composite catalysth ave ag reat influence on its photocatalytic activity.X RD can be used to characterizet he crystal phase structure and crystallinity of the photocatalyst.F igure 1 shows ac omparison of the XRD results of pure CdS nanosheets,p ureF e 3 O 4 NPs, and Fe 3 O 4 /PDA/CdS.…”
Section: Introductionmentioning
confidence: 99%
“…[58] This type of ultrathin nanosheet structurec an prevents urfaces ulfide ions from being oxidized, thereby effectively inhibiting photocorrosion. In addition, coupling CdS with other semiconductors, such as Ti 3 C 2 T x , [42a] Ni 2 S, [59] W 2 S, [60] ZnS, [61] Ag 2 S, [62] and WO 3 , [63] is an effective method to suppresst he recombination of photoinduced chargepairs. 111), (220), and (311) crystal faces of CdS, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] The oxidation process has been explored in various methodologies including traditional heating, [40][41][42][43][44] microwave irradiation, [39,[45][46][47] electrochemical method, [48][49][50][51][52] and ultrasonic irradiation. [53][54][55] Interestingly, though alcohol oxidation is reported by photocatalytic systems like Ag 2 S-CdS junction [56][57][58] and platinum nanocluster/graphitic carbon nitride, [59,60] however, use of copper complexes as photocatalyst remains rare and largely unexplored. [61,62] It is noteworthy to mention herewith that photocatalytic systems as a part of green synthetic processes have emerged as a research hotspot in current sustainable research scenario.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Ni-decorated Zn 0.5 Cd 0.5 S, Ni-modified CdS nanoparticles (NPs), and Ag 2 S-CdS p−n nanojunction have been used to efficiently split alcohols into hydrogen and the corresponding aldehydes or ketones in a stoichiometric manner with acetonitrile as the solvent under visible light. 11,12,21,22 C 3 N 4 photocatalysts decorated with Pt nanoparticles have been utilized for photocatalytic dehydrogenation of alcohols in acetonitrile and showed 72% conversion of benzhydrol and 98% selectivity of the product diphenyl ketone. 23 Wang et al reported a series of core−shell MOF@COF hybrids for selective oxidation of alcohols in acetonitrile and the highest conversion (94.7%) was 2.5 times that of NH 2 -MIL-125.…”
Section: Introductionmentioning
confidence: 99%